Hip spacers with a metal-on-cement articulation did not show significant surface alterations of the metal femoral head in two-stage revision for periprosthetic joint infection - Lunz, André; Sonntag, Robert; Kretzer, Jan Philippe; Jäger, Sebastian; Bormann, Therese; Streit, Marcus R.; Beckmann, Nicholas A.; Lehner, Burkhard; Omlor, Georg (Materials, 2020)
Two-stage revision is considered the gold standard treatment for chronic periprosthetic joint infection (PJI). During the interim period, between explantation of the infected hip endoprosthesis and revision arthroplasty, individually formed articulating hip spacers made of polymethylmethacrylate (PMMA) bone cement can be used to provide better soft tissue preservation, local antibiotic release, and improved postoperative mobilization. If effective prevention from luxation is achieved, hip function and hence overall patient satisfaction is improved. Zirconium oxide particles inside conventional PMMA bone cement, however, are known to enhance third-body wear, which may cause alterations of the metal head in the articulating spacer and hence become a serious risk for the patient. Therefore, the aim of our study was to analyze whether the articular surface of cobalt-chrome (CoCr) femoral heads is significantly altered in the setting of a metal-on-cement articulation during the interim period of two-stage revision for PJI. We analyzed a consecutive series of 23 spacer cases and compared them with femoral heads from two series of conventional hip arthroplasty revisions with metal-on-polyethylene articulations and different time intervals in situ. To investigate metallic wear, the femoral heads were thoroughly examined, and their surface roughness was measured and analyzed. We found no significant differences between the two conventional hip arthroplasty groups, despite their very different times in situ. Furthermore, the individually different times in situ within the spacer group had no significant impact on surface roughness, either. Compared with the spacer group, the surface roughness of the metal femoral heads from both conventional hip arthroplasty groups were even higher. Within the spacer group, roughness parameters did not show significant differences regarding the five predefined locations on the metal head. We conclude that metal-on-cement articulations do not cause enhanced surface alterations of the metal femoral head and hence do not limit the application in articulating hip spacers in the setting of two-stage revision for PJI.
Gesehen am 26.10.2020